Anti-programmed Cell Death Protein-1 Therapy in Intrahepatic Cholangiocarcinoma Induced Type 1 Diabetes: A Case Report and Literature Review - Zhi-Kai Zheng; Zhi-Kai Zheng; Jiong-Liang Wang; Jiong-Liang Wang; Wen-Xuan Li; Wen-Xuan Li; Tian-Qing Wu; Tian-Qing Wu; Min-Shan Chen; Min-Shan Chen; Zhong-Guo Zhou; Zhong-Guo Zhou (Frontiers Media S.A., 2022)
Immune checkpoint inhibitors, widely used in the treatment of malignancies, can improve the prognosis of patients, while it also can induce various immune-related adverse events, and type 1 diabetes induced by anti-programmed cell death protein-1 is a rare but severe complication. Here we reported a case of type 1 diabetes induced by anti-PD-1 which was to treat intrahepatic cholangiocarcinoma. The case was a 61-year-old female who developed diabetes and ketoacidosis symptoms at the 16th week after anti-PD-1 therapy. Her blood glucose was 30.32 mmol/L, HBA1c was 8.10%, and C-peptide was <0.10 ng/ml. The patient was diagnosed as fulminant type 1 diabetes mellitus complicated with ketoacidosis induced by anti-PD-1, and was treated with massive fluid rehydration, intravenous infusion of insulin and correction of acid-base electrolyte disorder. Hepatectomy was performed after stabilization, and the patient was treated with long-term insulin. Through the case report and literature review, this study aims to improve oncologists' understanding of anti-PD-1 induced type 1 diabetes, so as to make early diagnosis and treatment of the complications and ensure medical safety.